The United States Policy in Relation to Ethiopia, Democratic Republic Of The Congo, Sudan, South Sudan, Angola, and Libya - URNOV Andrey Yurievich (Ученые записки Института Африки Российской академии наук)
The political, economic and strategic significance of these six African countries have made them the object of intent attention and multivector activities by the United States of America. The article is focused on the events of 2019-2020. Despite an unprecedented internal political split and the coronavirus pandemic, the US African policy was sufficiently energetic, based on traditional “pillars” and conducted as part of the course for global hegemony.